THE CHINESE VECTOR IN THE MODERN FOREIGN POLICY OF RUSSIA: POLITICAL AND LEGAL ASPECT - V. V. Sevalnev; E. V. Cherepanova (Сравнительная политика, 2020)
The article is devoted to the study of Russian-Chinese relations at the present stage. The relations under consideration are dynamic, which is expressed in regular contacts at the highest level, cooperation in the international arena, including within the framework of international and regional organizations, trade and economic, humanitarian relations, common projects in the fi eld of military cooperation, etc. In this regard, the study and analysis of external and internal factors that contributed to the emergence, development, cooling, resumption and, ultimately, the formation of strategic partnership relations are important for the possible consideration of the Russian Federation in building further foreign policy relations with China and preventing previous mistakes.The authors studied and analyzed the defi ning directions and features of Russian-Chinese foreign policy relations, both in the historical context and at the present stage of development. In particular, the main periods in the development of bilateral relations are identifi ed; the factors that infl uenced the change of foreign policy strategies of the Russian Federation and the people's Republic of China are analyzed; the author reveals the nature of Russian-Chinese cooperation at the present stage, characterizes its role and importance both for regional policy and in the light of ongoing international processes, including in the fi eld of international security; identifi es possible risks that may adversely affect the nature of foreign policy cooperation between Russia and China.In conclusion, an attempt was made to formulate a possible forecast for the development of Russian-Chinese foreign policy relations, taking into account the current geopolitical situation in the world, as well as taking into account factors that can lead to contradictions between the two countries.